The key to intestinal health: a review and perspective on food additives - Wang, Haitao; Bai, Junyi; Miao, Pengyu; Wei, Yu; Chen, Xiaochao; Lan, Haibo; Qing, Yong; Zhao, Meizhu; Li, Yanyu; Tang, Rui; Yang, Xiangdong (Frontiers in Nutrition, 2024)
In this review, we explore the effects of food additives on intestinal health. Food additives, such as preservatives, antioxidants and colorants, are widely used to improve food quality and extend shelf life. However, their effects on intestinal microecology may pose health risks. Starting from the basic functions of food additives and the importance of intestinal microecology, we analyze in detail how additives affect the diversity of intestinal flora, oxidative stress and immune responses. Additionally, we examine the association between food additives and intestinal disorders, including inflammatory bowel disease and irritable bowel syndrome, and how the timing, dosage, and individual differences affect the body's response to additives. We also assess the safety and regulatory policies of food additives and explore the potential of natural additives. Finally, we propose future research directions, emphasizing the refinement of risk assessment methods and the creation of safer, innovative additives.